Unusual Roles of Secretory SNARE SYP132 in Plasma Membrane H+-ATPase Traffic and Vegetative Plant Growth. Issue 2 (29th March 2019) - Xia, Lingfeng; Mar Marquès-Bueno, Maria; Bruce, Craig Graham; Karnik, Rucha
Abstract : The secretory SNARE SYP132 affects auxin-regulated traffic of plasma membrane H + -ATPase proteins influencing plant growth and homeostasis. Abstract: The plasma membrane proton (H + )-ATPases of plants generate steep electrochemical gradients and activate osmotic solute uptake. H + -ATPase-mediated proton pumping orchestrates cellular homeostasis and is a prerequisite for plastic cell expansion and plant growth. All evidence suggests that the population of H + -ATPase proteins at the plasma membrane reflects a balance of their roles in exocytosis, endocytosis, and recycling. Auxin governs both traffic and activation of the plasma membrane H + -ATPase proteins already present at the membrane. As in other eukaryotes, in plants, SNARE-mediated membrane traffic influences the density of several proteins at the plasma membrane. Even so, H + -ATPase traffic, its relationship with SNAREs, and its regulation by auxin have remained enigmatic. Here, we identify the Arabidopsis ( Arabidopsis thaliana ) Qa-SNARE SYP132 (Syntaxin of Plants132) as a key factor in H + -ATPase traffic and demonstrate its association with endocytosis. SYP132 is a low-abundant, secretory SNARE that primarily localizes to the plasma membrane. We find that SYP132 expression is tightly regulated by auxin and that augmented SYP132 expression reduces the amount of H + -ATPase proteins at the plasma membrane. The physiological consequences of SYP132 overexpression include reduced apoplast acidification and suppressed vegetative growth. Thus, SYP132 plays unexpected and vital roles in auxin-regulated H + -ATPase traffic and associated functions at the plasma membrane.